Comparison of the neuraxial acoustic window in hamstring stretch position and cross-legged position: An observational pilot study - Priyanka Sethi; Manbir Kaur; N. Balakrishnan; Govind Singh; Deepanshu Dang; Kamlesh Kumari; Pradeep Kumar Bhatia (The Indian Anaesthetists' Forum)
Background: The patient’s position determines the success of the block during neuraxial anesthesia. We compare the neuraxial acoustic window in two positions namely, the hamstring stretch position (HSP) and the crossed-leg position, which are the modifications of sitting positions during spinal and epidural anesthesia. Methodology: This observational pilot study was conducted from October 2021 to November 2021 after approval from the ethics committee of our institution. Patients belonging to the age group 18–45 years were included. Forty patients were enrolled and each patient was asked to position him or herself in these two different sitting positions. Results: There was no statistically significant difference in the interlaminar distance (ILD) (P = 0.25), depth of ligamentum flavum (LF) from the skin, and intrathecal distance (P = 0.444) in these two sitting positions. The patients were more comfortable in the cross-leg position (P = 0.021). Conclusion: Both the positions, cross-leg position and HSP have no difference in ILD and depth of LF from the skin but patients were comfortable in cross-leg position.